EXPLORING THE HEALTH RECORDS MANAGEMENT SYSTEMS AND PATIENT SATISFACTION AT THE UNIVERSITY OF PORT HARCOURT TEACHING HOSPITAL, RIVERS STATE, NIGERIA - Isaruk , Justina Ikpoko-Ore-Ebirien Dike; Isaruk , Ikpoko-Ore-Ebirien Dike; Minkailu , Abubakar Amadu; Wosa , Sylvanus Amadioha (Global Journal of Medical and Health Science, 2025)
This study explores health record management systems (HRMS) and patient satisfaction at the University of Port Harcourt Teaching Hospital (UPTH), Rivers State, Nigeria. A cross-sectional survey design was adopted using structured questionnaires and interviews to gather data from a sample of 227 patients at various outpatient clinics. This study examined patients’ perceptions of the use of HRMSs including paper-based, electronic, and hybrid systems. Data analysis was conducted using descriptive statistics to identify trends and levels of satisfaction with health care services. The findings revealed that paper-based HRMS was the most prevalent, with patients expressing dissatisfaction with the hospital’s transition to electronic record management. Moreover, patient satisfaction levels were generally high, particularly in the general outpatient and health records management departments, despite challenges related to the hospital’s HRMS. The study concludes that the quality of HRMS plays a crucial role in patient satisfaction, recommending improvements in electronic health record (EHR) adoption and training of health care providers to enhance service delivery and patient outcomes.